2000
DOI: 10.1089/neu.2000.17.597
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Scan Features

Abstract: A. Which feature of the parameter is supported by class I and strong class II evidence and has at least a 70% positive predictive value in severe head injury? 1. Presence of abnormalities on initial CT examination. 2. CT classification. 3. Compressed or absent basal cisterns. 4. Traumatic subarachnoid hemorrhage (tSAH): • Blood in the basal cisterns. • Extensive tSAH. B. Parameter measurement:1. How should it be measured?• Compressed or absent basal cisterns measured at the midbrain level.• tSAH should be note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…The measurement of the MLS with CT scan was done twice for each patient (Figure 2 ): The first measurement (method 1) was taken in the same plane as the sonographic measurement: the distance between the external bone table and the centre of the third ventricle was measured from the CT slice among the 5-mm-wide cuts in the orbito-meatal plane that allowed visualising the third ventricle [ 30 ]. The second measurement (method 2), normally used by our neuroradiologists, measured the distance between the ideal mid line and the septum pellucidum [ 11 ], where the largest deviation was seen. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the MLS with CT scan was done twice for each patient (Figure 2 ): The first measurement (method 1) was taken in the same plane as the sonographic measurement: the distance between the external bone table and the centre of the third ventricle was measured from the CT slice among the 5-mm-wide cuts in the orbito-meatal plane that allowed visualising the third ventricle [ 30 ]. The second measurement (method 2), normally used by our neuroradiologists, measured the distance between the ideal mid line and the septum pellucidum [ 11 ], where the largest deviation was seen. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, a MLS above 0.5 cm on the initial brain CT scan has been shown to predict poor neurological outcome with a positive predictive value of 78% [ 2 ] whereas only 14% of cases without MLS on CT scan were shown to be associated with a poor outcome [ 3 ]. MLS on CT has been found to be correlated with the Glasgow coma score [ 4 - 6 ] and with other CT signs of injury severity (compressed basal cisterns, mass lesions or traumatic sub-arachnoid hemorrhage) [ 7 - 11 ]. A CT scan classification based on data from the Traumatic Coma Data Bank was proposed by Marshall et al [ 12 ], including a MLS >0.5 cm as one of the main CT criteria for the severity of traumatic brain injury (TBI) [ 12 , 13 ] and a multivariate analysis of a cohort of over 10,000 TBI patients showed that the compression of the third ventricle and a MLS >0.5 cm were both major predictors of mortality within the first 15 days after injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marshall et al, [49] in his publication on the Trauma Coma Data Bank, aggregated key findings on CT and proposed an imaging-based classification system of head injury that predicts mortality (Table 3). This system defines 4 types of diffuse head injury and takes the presence of a mass lesion and evidence of increased ICP (status of the basilar cisterns, presence of midline shift) into account.…”
Section: Role Of Imaging In the Prognostication Of Outcome Following Tbimentioning
confidence: 99%
“…(4, 810) This scale differentiates between types of mass lesions, recognizing the more favorable prognosis associated with epidural hematomas (EDH). (8, 12, 15) Although the Marshall CT score has been used in pediatric TBI research(11, 16, 17), neither it nor the Rotterdam CT score have been validated to predict mortality in children.…”
Section: Introductionmentioning
confidence: 99%